PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KOTA SIBOLGA (Lembaga Pengembangan Kinerja Dosen, 2022)
The sample in this study is the employees who are in the Dinas Pengendalian Penduduk dan Keluarga Berencana Kota Sibolga.The method used in this research is descriptive kuntitatif method by conducting multiple linear regression analysis test. This research is done by quantitative method. Data collection techniques used were questionnaires. Data analysis techniques used in this study is multiple linear regression using SPSS version 25 for windows. Style Leadership and Motivation simultaneously affect the performance of employees. Leadership style partially significant effect on employee performance, Motivation partially also have a significant effect on employee performance. Furthermore, the variable that has the most significant influence is the Leadership Style